2012
DOI: 10.1021/ja308249k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoresponsive Ultrathin Graphitic-Phase C3N4Nanosheets for Bioimaging

Abstract: Two-dimensional nanosheets have attracted tremendous attention because of their promising practical application and theoretical values. The atomic-thick nanosheets are able to not only enhance the intrinsic properties of their bulk counterparts but also give birth to new promising properties. Herein, we highlight an available pathway to prepare the ultrathin graphitic-phase C(3)N(4) (g-C(3)N(4)) nanosheets by a "green" liquid exfoliation route from bulk g-C(3)N(4) in water for the first time. The as-obtained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

58
1,309
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,009 publications
(1,379 citation statements)
references
References 35 publications
58
1,309
1
11
Order By: Relevance
“…In addition, it has been demonstrated that reduced-sized GCNNs and GCN quantum dots with much smaller lateral dimension can be used for bio-imaging due to their distinct fluorescence with low photo-bleaching and low cytotoxicity [21]. However, multilayer GCNNs reported so far have a low fluorescence quantum yield (less than 20%) [8,9,22], and GCN quantum dots show ignorable photocatalytic activity under visible light irradiation [23]. It is believed that nanosized monolayer graphitic carbon nitride nanosheets (NMGCNs) would be highly photo-responsive for both photocatalysis and fluorescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been demonstrated that reduced-sized GCNNs and GCN quantum dots with much smaller lateral dimension can be used for bio-imaging due to their distinct fluorescence with low photo-bleaching and low cytotoxicity [21]. However, multilayer GCNNs reported so far have a low fluorescence quantum yield (less than 20%) [8,9,22], and GCN quantum dots show ignorable photocatalytic activity under visible light irradiation [23]. It is believed that nanosized monolayer graphitic carbon nitride nanosheets (NMGCNs) would be highly photo-responsive for both photocatalysis and fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, GCNNs prepared with various techniques, such as mechanical milling [24,25], chemical oxidation thermal or etching [20,26,27], physical and liquid exfoliation [22,28,29], and electrochemical synthesis [30] usually show wide distributions in both the number of layers and lateral size. In particular, due to many advantages of easy operation, low-cost, environmental benignity, and no reason for interfacial defects, liquid-phase exfoliation, usually in conjunction with ultrasonic treatment has been intensively explored for producing ultrathin GCNNs by delaminating bulk GCN [28,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Since the booming development of graphene,1 freestanding 2D nanosheets with atomic thickness have drawn extensive attention from scientists due to their unique electronic structure and physical properties compared with their bulk counterparts 2, 3, 4, 5, 6. The atomically thick 2D nanomaterials show great promises in designing practical applications such as flexible and transparent electronic devices,7, 8 high‐performance in‐plane supercapacitor electrodes,9, 10, 11 and high‐efficiency catalysts 12, 13, 14.…”
mentioning
confidence: 99%
“…[19,30] Bulk graphitic-phase carbon nitride was synthetized by the polymerization of melamine molecules. CNNS was synthetized by sonicating bulk graphitic-phase carbon nitride in water, then the sonicated mixture was centrifuged at 5000 rpm to remove aggregated graphitic-phase carbon nitride particles to give a CNNS suspension, which was centrifuged at 15 000 rpm to acquire CNNS.…”
Section: Synthesis Of Cnnsmentioning
confidence: 99%
“…More recently, bulk graphitic-phase carbon nitride, a twodimensional layered graphene analogue, has been applied successfully in biological fields. [17,18] CNNS, which could be stripped from the bulk graphitic-phase carbon nitride, has also drawn increasing attention due to its unique properties [19,20] that include low Abbreviations used: Aβ , amyloid beta 42 peptide; CHA, catalytic hairpin assembly; CNNS, carbon nitride nanosheet; DMEM, Dulbecco's modified Eagle's medium; FAM, carboxyfluorescein; FAM-P1, FAM-labeled hairpin DNA probe 1 of CHA; FAM-P2, FAM-labeled hairpin DNA probe 2 of CHA; FL, fluorescence; GO, Graphene oxide; P1/P2-CNNS, CNNS simultaneously assembled with FAM-P1 and FAM-P2; P1-CNNS, CNNS assembled with FAM-P1; P2-CNNS, CNNS assembled with FAM-P2; PBS, phosphate-buffered saline; PC12 cells, pheochromocytoma cells; TEM, transmission electron micrograph. cytotoxicity, good biocompatibility and an efficient fluorescence quenching ability.…”
Section: Introductionmentioning
confidence: 99%